Determination of Optimum Strength of Red Soil and Mixed Soil using Soil-Cement (S/C) Mix Ratio - S Karki; S. Manandhar Manandhar; P. Voottipruex (International Association of Lowland Technology, 2020)
The research paper is focused on the improvement of the palaeolateritic red soil, clayey silt of low plasticity (ML) from Ratmatearea incorporating mixed with poorly graded sand with gravels(SP) from Helipad area inside the premises of Devghathydropower station, Nuwakot District, Nepal. With theconfirmation of maximum dry density (MDD) and optimummoisture content (OMC), 20% of SP was mixed homogenouslywith 80% of ML and experimented by adding cements at 3%,5%, 7% and 10% respectively. Hence ML and mixed soil(H20:R80) have been cured for 7, 14 and 28 days for thedetermination of undrained strength by UCS and pulse velocityby passing Pundit ultrasonic pulse velocity to check thecompactness of specimens. The Pearson’s coefficient ofcorrelation between UCS test and UPV revealed the strongpositive correlation linear relationship of 0.78. The linearregression model elucidates that for every additional undrainedstrength determined by UCS, the pulse velocity is expected to beenlarged by an average of 0.5135 m/s. Since, the cementadmixture of more than 7% impedes the rapid increase in pulsevelocity which was also confirmed by UCS tests due to thepresence of high capillary porosity of cement when excesscement was added. The study predicts that the optimum cementcontent for both soils in this research are best suitable at 7%admixture of cement when cured for 28 days.